Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Lesbianisme et féminisme : histoires politiques - Chetcuti, Natacha; Michard, Claire (L'Harmattan, 2003)
Cet ouvrage est le premier en France ayant pour objectif de rendre compte de l'interdépendance historique des mouvements lesbiens et des mouvements féministes à partir du point de vue de différents courants du lesbianisme. Il montre que l'histoire de la pensée lesbienne et féministe, des années 1970 à nos jours, est marquée par des alliances, des tensions et des ruptures qui ont des répercussions tant du côté des études universitaires que du côté des pratiques militantes. Il montre aussi que le contenu politique du lesbianisme, dans sa mise en cause de l'ordre établi, est constamment occulté.
Le texte de Brossard, Louise (2003). « Adrienne Rich et Monique Wittig : un point de départ pour penser l’hétérosexualité et les rapports sociaux de sexe » a été donné en lecture au cours POL4212.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; militance; pol4212; premier cycle; périodes historiques; systèmes d'oppressions; thématiques